The association between chronotype and social anxiety among Chinese university students: a moderated mediation analysis of loneliness and perceived social support - Yingying Zhu; Junling Liu; Fulin Chen; Qian Wang; Kunxia Cao; Jiahao Huang; He Wang; Qiang Wang; Xue Luo (BMC, 2024)
Abstract Background Social anxiety has been a burning problem among contemporary college students in China. Increasing evidence suggests that individual circadian typology-chronotype may play an important role in the development of social anxiety. However, little research has focused directly on examining the association between chronotype and social anxiety, and less is known about the mediating and moderating mechanisms underlying this relationship. The aim of the present study was to investigate the link between chronotype and social anxiety among Chinese college students, and to explore the mediating effect of loneliness and the moderating effect of perceived social support in the association between chronotype and social anxiety. Methods A cross-sectional design was conducted among 1616 college students (16-29 years old) from several public universities in Northern China, including 1172 females (72.52%) and 444 males (27.48%), with an average age of 19.68 years old (SD = 1.49). All participants completed the standardized self-report questionnaires including the Social Avoidance and Distress Scale, Morningness-Eveningness Questionnaire, UCLA Loneliness Scale, and the Perceived Social Support Scale. Common method bias was performed using Harman's single-factor test. The mediation and moderation effects were analyzed using SPSS software and PROCESS macros. Results Chronotype had a negative predictive effect on social anxiety in college students. Specifically, the greater the inclination of individuals' chronotypes toward evening preference, the more pronounced their symptoms of social anxiety would be. Loneliness served as a partial mediator in the relationship between chronotype and social anxiety, accounting for 30.0% of the total effect. In addition, perceived social support, particularly from friends and significant others, was found to play a moderating role in the process of loneliness affecting social anxiety among college students, while support from family did not. Interestingly, the perceived social support displayed a limited protective effect when college students suffered from higher levels of loneliness. Conclusion These findings deepened our understanding of how and when (or for "whom") chronotype is related to social anxiety, offering a theoretical foundation and practical insights for preventing and addressing social anxiety risk in young adult university students, particularly those with evening chronotypes.